HEMOLYTIC UREMIC SYNDROME - Ngurah Wisesa, Ida Bagus; Loekman, Jodi S (journal of internal medicine; Vol. 10, No. 1 Januari 2009)
Hemolytic uremic syndrome (HUS) is caused primarily by Shiga toxin–producing Escherichia coli O157:H7. Hemolytic uremic syndrome can occur in adults, and the most common cause of acute renal failure in children. Characteristic features of the syndrome are microangiopathic anemia, thrombotic thrombocytopenia, and renal failure. Although the presentation of this syndrome is diverse, the classic prodromal illness is bloody diarrhea. Children with HUS generally present with gastroenteritis complaints (e.g., abdominal pain or tenderness, nausea or vomiting, fever, anemia); affected adults may be asymptomatic. Complications from HUS can include intussusception, chronic renal failure, and seizures in severe cases. Because an incubation period of approximately one week occurs between the start of diarrhea and the onset of HUS, physicians should maintain a high index of suspicion; early laboratory testing is important to diagnose and manage this syndrome. Obtaining a complete blood count and stool culture and performing Shiga toxin testing are the first of a series of tests that may help diagnose of HUS.
Keywords: Hemolytic uremic syndrome (HUS) is caused primarily by Shiga toxin–producing Escherichia coli O157:H7. Hemolytic uremic syndrome can occur in adults, and the most common cause of acute renal failure in children. Characteristic features of the syndrome are